Post-transplant kidney atelectasis: Case report - Rodrigues, Naiara Oliveira; Silva, Graziella Alves da; Stella, Thamiê Cristina; Almeida, Marley Cintra de; Chiavegato, Luciana Dias (Brazilian Journal of Transplantation, 2019)
Introduction: Studies show that the incidence of atelectasis in patients under general anesthesia is 50% to 90%. This occurs 5 to 10 minutes after anesthetic induction persisting for several postoperatively days. Purpose: To describe the result of the association of breathing exercises, non-invasive ventilation and mobilization as physical therapy resources applied to a patient with total right lung atelectasis, three days after kidney transplantation. Methods: Retrospective, descriptive study of a case of a 42-year-old female smoker patient admitted to a tertiary hospital. On the third postoperative day after kidney transplantation, she developed total atelectasis in the right hemithorax, dyspnea, oxygen desaturation (Spo2: 88%), and persistent left dependent ventilatory pain. Physiotherapy was performed for 4 days, 8 sessions of 60 minutes each in July 2018. Treatment consisted of bronchial hygiene maneuvers, pulmonary reexpansion exercises associated with noninvasive ventilation (BINIVEL-EPAP: 14 and IPAP: 16) and ambulation. Results: Atelectasis was confirmed, confirmed by chest X-ray, and respiratory parameters improved, as well as pulmonary auscultation after each session and throughout treatment. Conclusion: The association of physical therapy resources demonstrated to be able to revert atelectasis presented by a patient in the post-transplant period.